Interferon-alpha/beta receptor deficiency enhances susceptibility to Powassan virus infection in mice - Elsharkawy, Amany; Pathak, Heather; Dim, Chinonye; Kumar, Mukesh (Frontiers in Microbiology, 2025)
Powassan virus (POWV) is a tick-borne flavivirus that causes neurotropic disease in humans. POWV causes fatal encephalitis and meningitis in 10% of human cases and long-term neurological sequelae in 50% of surviving patients. While innate antiviral responses have been extensively studied in mosquito-borne flavivirus infections, they remain less well characterized in the context of tick-borne flaviviruses. In this study, we investigated the role of interferon α/β receptor in the pathogenesis of POWV infection in vivo. Herein, we showed that unlike wild-type (WT) mice, interferon α/β receptor-deficient (Ifnar−/−) mice were highly susceptible to POWV and rapidly succumbed to infection. Low inoculum dosage resulted in 100% mortality rate in Ifnar−/− mice early after infection. Higher levels of viremia accompanied by increased serum levels of proinflammatory cytokines and chemokines were observed in Ifnar−/− mice. Further, we detected significantly higher virus levels in the peripheral tissues including spleen, liver and kidney in Ifnar−/− mice compared to WT mice. Subsequent analyses revealed marked pathology and elevated inflammatory responses in the peripheral organs of Ifnar−/− mice. Additionally, Ifnar−/− mice showed a stunted immune response in the spleen with significantly decreased numbers of B cells, monocytes, and neutrophils. While WT mice exhibited increased splenic accumulation of Ly6C+ cells, this recruitment was markedly impaired in Ifnar−/− mice. Notably, viral load quantification and immunofluorescence analysis showed no significant difference in brain viral load between WT and Ifnar−/− mice; however, Ifnar−/− mice displayed elevated inflammatory response in the brain. These data suggest that the rapid mortality observed in Ifnar−/− mice is due to uncontrolled virus dissemination and excessive inflammation in the periphery rather than brain infection. Collectively, our data reveal that the type-I interferon response restricts viral tropism and pathogenesis of POWV in mice.